Satisfaction among dairy farm owners after certification on good management practices (2018)
ABSTRACT:The adoption of good management practices (GMP) in dairy farming implies changes that generate satisfaction for the personnel involved in the milk production process. The objective of this study was to assess the level of satisfaction obtained among GMP-certified producers. A total of 37 farm owners in northern Antioquia were surveyed. Data were analyzed using factor analysis and structural equations. A “General satisfaction” variable was analyzed using recursive partitioning and regression trees. Producers were satisfied with the GMP certification, mostly with the changes achieved in working conditions, interrelationships and staff training. The GMP satisfy owners by generating positive changes in the working conditions of the personnel, providing permanent training, and improving their image to other farmers and milk-buying companies.